High-strength separator

The production of polyolefin microporous membranes using UHMWPE and a plasticizer, combined with controlled processing, addresses the challenges of strength and stability in lithium-ion battery separators, enhancing mechanical integrity and resistance to compression.

JP7621417B2Active Publication Date: 2025-01-24ASAHI KASEI BATTERY SEPARATOR CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023089795
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-09-25
Filing Date
2023-05-31
Publication Date
2025-01-24
Estimated Expiration
2039-09-25

AI Technical Summary

Technical Problem

Existing polyolefin microorganism membranes for lithium-ion batteries face challenges in achieving high strength and stability due to the difficulty in molding ultra-high molecular weight polyethylene, leading to issues with molecular weight deterioration and mechanical integrity.

Method used

A method involving the production of a polyolefin microporous membrane using a mixed slurry of ultra-high molecular weight polyethylene (UHMWPE) and a plasticizer, followed by specific processing steps including extrusion, stretching, and heat treatment to achieve a cross-sectional crystal orientation of 0.85 or more, with controlled pore size and crystallinity, resulting in a separator with enhanced mechanical strength and resistance to compression.

Benefits of technology

The proposed method produces a separator with improved mechanical strength, resistance to compression, and reduced molecular weight deterioration, ensuring high-quality performance in lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007621417000007
    Figure 0007621417000007
  • Figure 0007621417000001
    Figure 0007621417000001
  • Figure 0007621417000002
    Figure 0007621417000002
Patent Text Reader

Abstract

To provide a separator for a power storage device having usable quality and strength, or a microporous polyolefin membrane for forming the separator.SOLUTION: In a polyolefin microporous membrane used for separators for power storage devices, The polyethylene crystallinity of the polyolefin microporous membrane measured by X-ray diffraction (XRD) is 80 to 99%, and the polyethylene crystallinity size of the polyolefin microporous membrane measured by XRD is 14.2 to 40.0 nm, and the degree of cross-sectional crystallinity of the microporous polyolefin membrane is 0.80 to 0.99.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a separator for an electricity storage device, a method for producing a separator for an electricity storage device, a method for producing a polyolefin microporous membrane, and the like. [Background technology]

[0002] Microporous membranes are widely used as separation or permselective separation membranes for various substances, separators, etc., and examples of their applications include precision filtration membranes, separators for fuel cells and capacitors, base materials for functional membranes in which functional materials are filled into the pores to exhibit new functions, separators for electricity storage devices, etc. Among these, polyolefin microporous membranes are suitably used as separators for lithium ion batteries, which are widely used in notebook personal computers, mobile phones, digital cameras, etc.

[0003] Generally, polyolefin microporous membranes are produced using polyethylene with a relatively low molecular weight. In recent years, however, attempts have been made to produce polyolefin microporous membranes usable as lithium ion battery separators using polyethylene with a relatively high molecular weight (Patent Documents 1 to 3).

[0004] In Patent Document 1, a separator for an electric storage device is described that is made of a first polyethylene having a weight average molecular weight of 1,000,000 or more and a density of 0.942 g / cm in order to prevent a phenomenon in which the electrolyte is not retained in the pores of the separator (so-called liquid drying-up) while maintaining the mechanical strength and shutdown characteristics of the separator. 3 The use of the above second polyethylenes in combination has been proposed; specifically, in the production of a polyethylene microporous membrane, a first polyethylene powder having a weight average molecular weight of 4,150,000 and a melting point of 141°C and a second polyethylene powder having a weight average molecular weight of 560,000 and a melting point of 135°C are used.

[0005] Patent Document 2 describes that in order to prevent poor cutting when cutting a separator for a nonaqueous electrolyte battery with a blade and to achieve excellent shutdown characteristics, a polyethylene having a weight average molecular weight of 500,000 or more is used as the main component of the separator, and the area ratio I(110) / (I(110)+I(200)), which is represented by the area I(110) of the diffraction peak of the (110) plane and the area I(200) of the diffraction peak of the (200) plane when the separator is irradiated with X-rays in the thickness direction, is adjusted to 0.90 or more.

[0006] Patent Document 3 describes a method for producing a polyolefin microporous membrane, which includes the steps of melt-kneading a resin composition containing a polyolefin resin having a weight-average molecular weight of 500,000 or more and liquid paraffin, forming the resulting molten mixture into a sheet, and rolling and removing the liquid paraffin from the resulting sheet-like molded product. It proposes that the resin composition be stirred in advance with a stirrer equipped with a butterfly blade rotating at 10 to 500 rpm and a turbine blade rotating at 500 to 3000 rpm, and then subjected to melt-kneading. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] International Publication No. 2011 / 118660 [Patent Document 2] JP 2017-103044 A [Patent Document 3] JP 2002-88189 A Summary of the Invention [Problem to be solved by the invention]

[0008] In the field of microporous membranes, ultra-high molecular weight polyethylene (UHMWPE) is notoriously difficult to mold.

[0009] In providing a polyolefin microporous membrane using ultra-high molecular weight polyethylene having a viscosity average molecular weight Mw of 300,000 to 900,000 and a degree of dispersion (weight average molecular weight Mw / number average molecular weight Mn) of 3 to 15, the techniques described in Patent Documents 1 and 2 still have room for improvement in terms of qualities as a separator for an electricity storage device, such as less gel, suppression of molecular weight deterioration, battery safety and cyclability, and separator strength, such as tensile strength and puncture strength.

[0010] The method for producing a polyolefin microporous membrane described in Patent Document 3 involves a polyolefin resin having a weight-average molecular weight of 500,000 or more, and therefore there is still room for further study on the conditions under which each step can be carried out. In addition, the polyolefin microporous membrane obtained by the method described in Patent Document 3 has room for improvement in terms of the quality as a separator for a lithium ion battery, such as less gel and suppression of molecular weight deterioration, and in the separator strength, such as tensile strength and puncture strength.

[0011] In view of the above circumstances, an object of the present invention is to provide a separator for an electricity storage device having usable quality and strength, or a polyolefin microporous membrane for forming the same. [Means for solving the problem]

[0012] The present inventors have found that the above problems can be solved by specifying the crystallinity of polyethylene used in a separator for an electricity storage device by X-ray diffraction (XRD), or by extruding and molding a mixed slurry of a liquid plasticizer and ultra-high molecular weight polyethylene (UHMWPE) under specific conditions and making the resulting molded product porous, and have completed the present invention. That is, the present invention is as follows. [1] A separator for an electricity storage device, having a cross-sectional crystal orientation degree of 0.85 or more. [2] The separator for the power storage device is 1 nm 3 The specific surface area S per unit is 1×10 -2 nm 2 ~5×10 -2nm 2 2. The separator for an electricity storage device according to item 1, [3] 3. The separator for an electricity storage device according to item 1 or 2, wherein the separator for an electricity storage device has a converted average pore size calculated according to Porod's law in a small angle X-ray scattering (SAXS) measurement of the separator for an electricity storage device of 50 nm to 150 nm. [4] 4. The electricity storage device separator according to any one of items 1 to 3, wherein the electricity storage device separator contains polyethylene (PE) and has a polyethylene crystallite size of 14.2 nm to 40.0 nm. [5] 5. The separator for an electricity storage device according to any one of items 1 to 4, wherein the separator for an electricity storage device contains ultra-high molecular weight polyethylene (UHMWPE). [6] 6. The separator for an electricity storage device according to any one of items 1 to 5, wherein the cross-sectional crystal orientation degree is 0.99 or less. [7] A polyolefin microporous membrane comprising ultra-high molecular weight polyethylene (UHMWPE) having a viscosity average molecular weight (Mv) of 300,000 to 9,000,000 and a dispersity (Mw / Mn) expressed as the ratio of weight average molecular weight (Mw) to number average molecular weight (Mn) of 3 to 15, The polyolefin microporous membrane is used for a separator for an electricity storage device, and is characterized in that the polyolefin microporous membrane has a polyethylene crystallinity of 80 to 99% measured by X-ray diffraction (XRD) and a polyethylene crystallite size of 14.2 to 40.0 nm measured by XRD. [8] 8. The polyolefin microporous membrane according to item 7, wherein the polyolefin microporous membrane has a cross-sectional crystal orientation degree of 0.80 to 0.99. [9] Item 9. The polyolefin microporous membrane according to item 7 or 8, wherein the polyolefin microporous membrane has a converted average pore diameter calculated according to Porod's law in a small angle X-ray scattering (SAXS) measurement of the polyolefin microporous membrane is 50 to 150 nm.

[10] Formula 6 below: 10 μm converted permeability coefficient (J) = air permeability (Pe) ÷ porosity (Po) (Equation 6) 10. The polyolefin microporous membrane according to any one of items 7 to 9, having a converted permeability coefficient per 10 μm of membrane thickness, expressed as:

[11] 11. The polyolefin microporous membrane according to any one of items 7 to 10, wherein the UHMWPE is poly(ethylene and / or propylene-co-α-olefin).

[12] The polyolefin microporous membrane according to any one of items 7 to 11, wherein the UHMWPE is at least one selected from the group consisting of poly(ethylene-co-propylene), poly(ethylene-co-butene), and poly(ethylene-co-propylene-co-butene).

[13] 13. The polyolefin microporous membrane according to any one of items 7 to 12, wherein the UHMWPE contains 98.5 mol % or more and 100 mol % or less of structural units derived from ethylene.

[14] 14. The polyolefin microporous membrane according to any one of items 7 to 13, wherein the UHMWPE contains more than 0.0 mol % and not more than 1.5 mol % of structural units derived from an α-olefin other than ethylene.

[15] 15. The polyolefin microporous membrane according to any one of items 7 to 14, wherein the mass ratio of the UHMWPE is 2 mass% to 90 mass% based on the total mass of all powder raw materials of the polyolefin microporous membrane.

[16] Item 16. The polyolefin microporous membrane according to any one of items 7 to 15, wherein the mass ratio of the UHMWPE is 5 mass% to 70 mass% based on the total mass of all powder raw materials of the polyolefin microporous membrane.

[17] A method for producing a polyolefin microporous membrane for use as a separator for a lithium ion secondary battery, comprising the steps of: (1) Temperature: 20℃~70℃, 100 seconds -1~400,000 seconds -1 and a residence time of 1.0 to 60 seconds, using a continuous mixer to mix a polyolefin powder containing polyethylene (PE) and a plasticizer to produce a mixed slurry; (2) feeding the mixed slurry into a twin-screw extruder and extruding it to produce a resin composition; (3) a step of extruding the resin composition into a sheet, cooling and solidifying it to process it into a sheet-like molded product; (4) biaxially stretching the sheet-like molded body at an areal magnification of 20 times or more and 200 times or less to form a stretched product; (5) extracting the plasticizer from the stretched product to form a porous body; and (6) a step of heat-treating the porous body at a temperature equal to or lower than the melting point of the porous body to stretch the porous body; A method for producing a polyolefin microporous membrane, comprising:

[18] Item 18. The method for producing a polyolefin microporous membrane according to Item 17, wherein in the step (2), the polyolefin powder is swelled, melted, and / or kneaded in the twin-screw extruder.

[19] Item 19. The method for producing a polyolefin microporous membrane according to Item 17 or 18, wherein the polyethylene is ultra-high molecular weight polyethylene (UHMWPE), and the content of the UHMWPE in the polyolefin powder is 2% by mass to 90% by mass based on the mass of the polyolefin powder.

[20] 20. The method for producing a polyolefin microporous membrane according to any one of items 17 to 19, wherein the polyethylene is ultra-high molecular weight polyethylene (UHMWPE), and the UHMWPE has a viscosity average molecular weight (Mv) of 300,000 to 9,700,000 and a molecular weight distribution (Mw / Mn) expressed as the ratio of weight average molecular weight (Mw) to number average molecular weight (Mn) of 3 to 15. [twenty one] 21. The method for producing a polyolefin microporous membrane according to any one of items 17 to 20, wherein in the step (2), the mixed slurry is fed to the twin-screw extruder at a temperature of 25°C to 80°C to produce the resin composition. [twenty two] 22. The method for producing a polyolefin microporous membrane according to any one of items 17 to 21, wherein in the step (6), the porous body is stretched in the width direction and / or the length direction. Effect of the Invention

[0013] According to the present invention, it is possible to provide a separator for an electricity storage device having high quality and high strength, and a polyolefin microporous membrane used therein, and further to improve the compression resistance in the thickness (cross-sectional) direction of the separator for an electricity storage device or the polyolefin microporous membrane. Furthermore, since the present invention can subject the mixed slurry to the extrusion step, it is possible to suppress deterioration of the molecular weight and / or to provide excellent handleability, compared to supplying a powder or solid mixture. [Brief description of the drawings]

[0014] [Figure 1] FIG. 1 is a graph showing the relationship between the diffraction angle and the diffraction intensity in X-ray diffraction (XRD) of a polyolefin microporous membrane according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] Hereinafter, a detailed description will be given of an embodiment of the present invention (hereinafter, abbreviated as "embodiment"). Note that the present invention is not limited to the following embodiment, and can be modified in various ways within the scope of the present invention. Unless otherwise specified, the physical properties or evaluation values ​​described in this specification are measured or calculated according to the methods described in the examples.

[0016] <Separators for power storage devices> A separator for an electricity storage device (hereinafter, also simply referred to as "separator") is required to have insulating properties and lithium ion permeability, and is therefore generally formed from an insulating material having a porous structure, such as paper, a polyolefin nonwoven fabric, or a resin microporous film. In particular, for lithium ion batteries, a polyolefin microporous film is excellent because it is resistant to oxidation-reduction deterioration of the separator and can form a dense and uniform porous structure.

[0017] The separator may be in the form of a flat membrane (e.g., formed from a single microporous membrane), a laminated membrane (e.g., a laminate of multiple polyolefin microporous membranes, or a laminate of a polyolefin microporous membrane and another membrane), a coated membrane (e.g., a polyolefin microporous membrane with at least one side coated with a functional substance), or the like.

[0018] The separator according to the first embodiment has a cross-sectional crystal orientation of 0.85 or more. When the separator has a cross-sectional crystal orientation of 0.85 or more, the separator tends to achieve both separator quality, such as less gel, suppression of molecular weight degradation, battery safety and cycle performance, and separator strength, such as compression resistance in the separator's thickness (z) direction, tensile strength, and puncture strength. In particular, the effect of compression resistance in the thickness (cross-sectional) direction has the following industrial value.

[0019] In recent years, with the increase in capacity of lithium-ion batteries, the active material used in the electrodes has been changed from the conventional 1:1:1 ratio of nickel:manganese:cobalt in the positive electrode to a high-nickel type with a nickel:manganese:cobalt ratio of 8:1:1, and in some cases even higher. The negative electrode material has been changed from graphite to silicon or a silicon-containing type, which has led to the development of high-density batteries. However, in either case, the electrodes expand and contract significantly during the battery charge and discharge process, applying a compressive force to the separator, which reduces the separator's film thickness and increases its air permeability, resulting in a decrease in ion conductivity and a deterioration in cycle characteristics.

[0020] Meanwhile, the manufacturing process for automotive batteries often involves compressing the laminated state of electrodes and separators. In recent years, in particular, there are cases in which the materials are compressed while being heated in order to improve adhesion between the materials and increase production speed.

[0021] Therefore, in order to realize a battery that can be used for a long time without deteriorating the physical properties of the separator even during the battery production process, the present invention provides a separator that exhibits good compression resistance (no film thickness reduction) under compression conditions in a specific direction, for example, in the thickness (cross-section, z) direction, and from the viewpoint of polymer chemistry, the most important control factor for maintaining the resistance is the degree of cross-sectional crystal orientation, and as another control factor, the degree of cross-sectional crystal orientation of 1 nm of the separator is found. 3 The specific surface area per unit area (S), the converted average pore size, and the polyethylene crystallite size were found.

[0022] The cross-sectional crystal orientation can be calculated by wide-angle X-ray scattering measurement of a single film sample by the transmission method described in the Examples.

[0023] In this specification, when the separator is a flat membrane, the separator is subjected to X-ray scattering or X-ray diffraction measurement. When the separator is a laminated membrane, one membrane sample is removed from the laminated membrane and subjected to X-ray scattering or X-ray diffraction measurement. When the separator is a coating membrane, the coating membrane is subjected to X-ray scattering or X-ray diffraction measurement. X-ray scattering measurement and X-ray diffraction measurement can be performed by the method described in the examples.

[0024] When the separator has a cross-sectional crystal orientation degree of ≧0.85 in wide-angle X-ray scattering measurement, while not wishing to be bound by theory, it is believed that the c-axis is randomly oriented on the projection surface, whereas the c-axis is oriented generally parallel to the surface of the membrane sample on the cross section, and the crystalline phase approaches complete orientation (i.e., the amorphous phase also approaches complete orientation), thereby making it resistant to stress from a specific direction, for example, compression from the thickness (z) direction. From the viewpoints of compression resistance and mechanical strength in the z direction, the cross-sectional crystal orientation degree of the separator is preferably 0.86 or more or 0.87 or more, and preferably 0.88 or more or 0.89 or more. In addition, from the viewpoints of handleability and flexibility during device fabrication, the cross-sectional crystal orientation degree of the separator is preferably 0.99 or less, more preferably 0.98 or less or 0.97 or less.

[0025] In the first embodiment, the separator is 1 nm 3 From the viewpoint of improving the separator quality and compression resistance in the z direction, the specific surface area (S) per unit area is set to 1×10 -2 nm 2 ~5×10 -2 nm 2 It is preferable that the ratio is 1.4×10 -2 nm 2 ~4.5×10 -2 nm 2 It is more preferable that the specific surface area (S) is the specific surface area per unit volume of the separator on the nano-order, and can be controlled by the three-dimensional structure or internal structure of the separator. When the separator includes a microporous membrane, the specific surface area (S) can also be controlled by adjusting the microporosity. 3 The specific surface area S per unit area is measured during small angle X-ray scattering measurement by the transmission method described in the Examples.

[0026] In the small angle X-ray scattering (SAXS) measurement of the separator according to the first embodiment, the converted average pore size calculated according to the Porod's law is preferably 50 nm to 150 nm, and more preferably 55 nm to 145 nm or 91 nm to 136 nm from the viewpoint of improving the compression resistance, tensile strength and puncture strength in the z direction. The reason why this range is preferable is not clear, but it is considered that the mechanical strength of the separator is strongly influenced by the average pore size, and that this range particularly contributes to stress dispersion and prevents stress concentration on specific defects in the sample membrane to be measured from the relationship between the membrane thickness range (25 μm or less) usually used as a lithium ion battery separator and the crystallite size of the present invention. Furthermore, it is considered that the ease of passage of lithium ion clusters inside the membrane in the battery is strongly correlated with the size of the clusters and the average pore size of the actual membrane measured by SAXS without contact, and as a result, the ionic resistance can be adjusted to an appropriate range. In addition, in this range of average pore size, the cycle characteristics are good and the resistance during charging and discharging is low, so it is presumed that the solid electrolyte interface (SEI) is formed extremely uniformly on the electrode surface during initial charging and discharging. The method for calculating the converted average pore size according to Polod's law in small-angle X-ray scattering measurement is described in detail in the section on Examples.

[0027] When the separator according to the first embodiment contains polyethylene, it is preferable that the polyethylene crystallite size is 14.2 nm to 40.0 nm when measured by X-ray diffraction (XRD) of the separator. In the XRD of polyethylene, the crystallite size represents the thickness of the crystal in the direction perpendicular to the polyethylene molecular chain. When the polyethylene crystallite size is within the range of 14.2 nm to 40.0 nm, it is considered that the cleavage points in the polyethylene are diffused, and stress concentration can be suppressed, and therefore it is likely that the separator for the electric storage device can achieve a usable level of quality, strength, and compression resistance in the z direction. This tendency is remarkable when the separator contains ultra-high molecular weight polyethylene (UHMWPE), which has been difficult to mold in the past.

[0028] In order to further improve the quality and compression resistance in the z-direction of the separator, the polyethylene crystallite size in the XRD measurement of the separator is preferably 15.0 nm to 35.0 nm, more preferably 15.5 nm to 36.5 nm, and further preferably 16.0 nm to 36.0 nm. The XRD can be performed by the method described in the Examples.

[0029] The components of the separator are described below.

[0030] <Polyolefin microporous membrane> The polyolefin microporous membrane according to the second embodiment contains ultra-high molecular weight polyethylene (UHMWPE). In this specification, ultra-high molecular weight polyethylene (UHMWPE) refers to polyethylene having a viscosity average molecular weight (Mv) of 300,000 to 9,000,000 and a polydispersity (Mw / Mn) expressed as the ratio of weight average molecular weight (Mw) to number average molecular weight (Mn) of 3 to 15.

[0031] Since the polyolefin microporous membrane has resistance to oxidation-reduction degradation and a dense and uniform porous structure, it can be used in a separator for an electricity storage device, can be contained in a separator, can be used as a flat membrane to form a separator, etc. Also, the polyolefin microporous membrane according to the second embodiment can form the separator according to the first embodiment.

[0032] The polyolefin microporous membrane according to the second embodiment is characterized in that, when measured by X-ray diffraction (XRD), the polyethylene crystallinity is 80% to 99% and the polyethylene crystallite size is 14.2 nm to 40.0 nm. In the XRD of polyethylene, the crystallinity represents the proportion of the crystalline phase in the polyethylene, and the crystallite size represents the thickness of the crystal in the direction perpendicular to the polyethylene molecular chain. In this specification, the polyethylene measured by XRD of the polyolefin microporous membrane can include not only UHMWPE but also polyethylene other than UHMWPE.

[0033] By having the degree of crystallinity of the polyethylene be in the range of 80% to 99% and the crystallite size be in the range of 14.2 nm to 40.0 nm, it is possible to provide a microporous film having the quality and strength usable for a separator for an electricity storage device using UHMWPE, which has been difficult to mold in the past. In relation to this, although the degree of crystallinity of the polyethylene is relatively high (i.e., the amorphous phase is relatively small), the crystallite size is 14.2 nm to 40.0 nm, so it is considered that the cleavage points in the polyethylene are diffused, thereby suppressing stress concentration.

[0034] To further improve the quality and strength of the polyolefin microporous membrane used in the separator for the electricity storage device, in XRD measurement of the polyolefin microporous membrane, the polyethylene crystallinity is preferably 82% to 97%, more preferably 84% to 96% or 86% to 94%, and / or the polyethylene crystallite size is preferably 15.0 nm to 35.0 nm, more preferably 15.5 nm to 36.5 nm, and even more preferably 16.0 nm to 36.0 nm. The XRD of the polyolefin microporous membrane can be performed by the method described in the Examples.

[0035] The cross-sectional crystal orientation of the polyolefin microporous membrane is preferably 0.80 to 0.99, more preferably 0.81 to 0.98, and even more preferably 0.85 to 0.97 or 0.89 to 0.97, from the viewpoints of exhibiting good flexibility from the viewpoint of handling when producing a device using the separator for an electricity storage device and obtaining high mechanical strength. The cross-sectional crystal orientation can be calculated by wide-angle X-ray scattering measurement of the polyolefin microporous membrane by a transmission method. The wide-angle X-ray scattering measurement can be performed by the method described in the Examples.

[0036] Regarding the wide-angle X-ray scattering measurement of polyethylene, although we do not wish to be bound by theory, the following (1) to (3): (1) In the crystal structure of polyethylene, the c-axis <001> Face and <110> Because the faces are orthogonal, observing the orientation of one face can tell you the orientation of the other face; (2) <110> The orientation of the plane is <110> from the azimuthal spread of scattering from a surface; and (3) <110> The full width at half maximum of the azimuth angle-scattering intensity plot is an effective way to quantify the orientation of the planes; the sharper the full width at half maximum, the higher the degree of orientation of the polyethylene molecular chains; It is possible that: Considering the above (1) to (3), when the cross-sectional crystal orientation degree is adjusted to be within the range of 0.80 to 0.99 in wide-angle X-ray scattering measurement of polyethylene, the c-axis is randomly oriented on the projection plane, whereas the c-axis is oriented roughly parallel to the surface of the polyolefin microporous membrane on the cross section, with the crystalline phase approaching perfect orientation (i.e., the amorphous phase also approaches perfect orientation), which is thought to enable the membrane to withstand stress from a specific direction.

[0037] In the small angle X-ray scattering (SAXS) measurement of the polyolefin microporous membrane, the converted average pore size calculated according to the Polod's law is preferably 50 nm to 150 nm, and more preferably 55 nm to 145 nm or 91 nm to 136 nm from the viewpoint of improving the tensile strength and the pin puncture strength. The reason why this range is preferable is not clear, but the mechanical strength of the polyolefin microporous membrane is strongly affected by the average pore size, and from the relationship between the membrane thickness range (25 μm or less) usually used as a lithium ion battery separator and the crystallite size of the present invention, this range is particularly likely to contribute to stress dispersion and prevent stress concentration on specific membrane defects. Furthermore, it is considered that the ease of passage of lithium ion clusters inside the membrane in the battery is strongly correlated with the size of the cluster and the average pore size of the actual membrane measured by the above SAXS measurement in a non-contact state, and as a result, the ion resistance can be adjusted to a moderate range. In addition, in this average pore size range, the cycle characteristics are good and the resistance during charging and discharging is low, so it is also speculated that the SEI is formed extremely uniformly on the electrode surface during initial charging and discharging. The method for calculating the converted average pore size according to Porod's law in small angle X-ray scattering measurement will be described in detail in the Examples section.

[0038] For general measurement of pores in porous bodies, gas adsorption (1-100 nm) and mercury porosimetry (1-100 μm) are known. The separator used in the second embodiment has a structure in which meso-macro coexist, and it is considered that it cannot be measured by the gas adsorption method. On the other hand, the mercury porosimetry is adapted to the measurement range of the polyethylene microporous membrane used in the second embodiment, but since a relatively high pressure is applied to the membrane during measurement, the polyethylene microporous membrane is crushed and the structure is destroyed, so it is considered that it cannot be measured. Furthermore, in addition to the gas adsorption method and the mercury porosimetry, there is a method (through pore size distribution measurement) in which the air permeability or water permeability is measured to calculate the pore size and tortuosity according to a tube model, but the separator used in the second embodiment has a very complicated porous structure, so there is no engineering model that can accurately depict it. In the second embodiment, the porous structure of the polyethylene microporous membrane can be statistically measured nondestructively and accurately by using the X-ray structure analysis, and can be related to the battery cycle performance or safety evaluation performance.

[0039] From the viewpoint of high quality and strength sufficient for use as a separator for an electricity storage device, the polyolefin microporous membrane is one having a molecular weight of 1.0 or more and a molecular weight of 1.0 or more. 10 μm converted permeability coefficient (J) = air permeability (Pe) ÷ porosity (Po) (Equation 6) The converted permeability coefficient per 10 μm of film thickness represented by the following formula is preferably 0.5 to 14, and more preferably 0.7 to 13.8.

[0040] The properties of the polyolefin microporous membrane are described below. These properties are for the case where the polyolefin microporous membrane used as the separator for an electricity storage device is a flat membrane, but when the separator for an electricity storage device is in the form of a laminated membrane, the properties can be measured after removing layers other than the microporous membrane from the laminated membrane.

[0041] The porosity of the polyolefin microporous film is preferably 20% or more, more preferably 30% or more, and even more preferably 31% or more. When the porosity of the microporous film is 20% or more, the followability to the rapid movement of lithium ions tends to be improved. On the other hand, the porosity of the microporous film is preferably 90% or less, more preferably 80% or less, and even more preferably 50% or less. When the porosity of the microporous film is 90% or less, the film strength tends to be improved and self-discharge tends to be suppressed. The porosity of the microporous film can be measured by the method described in the Examples.

[0042] The air permeability of the microporous polyolefin membrane is 100 cm 3 The air permeability of the microporous membrane is preferably 1 second or more, more preferably 50 seconds or more, even more preferably 55 seconds or more, even more preferably 60 seconds or more, 100 seconds or more, 120 seconds or more, 140 seconds or more, or 150 seconds or more per second. When the air permeability of the microporous membrane is 1 second or more, the balance between the membrane thickness, the porosity, and the average pore size tends to be further improved. In addition, the air permeability of the microporous membrane is preferably 400 seconds or less, more preferably 320 seconds or less, even more preferably 310 seconds or less, 300 seconds or less, 280 seconds or less, or 270 seconds or less. When the air permeability of the microporous membrane is 400 seconds or less, the ion permeability tends to be further improved. The air permeability of the microporous membrane can be measured by the method described in the Examples.

[0043] The tensile strength of the polyolefin microporous membrane is preferably 1000 kgf / cm in both MD and TD (direction perpendicular to MD, membrane width direction). 2 More preferably, it is 1050 kgf / cm 2 More preferably, it is 1100 kgf / cm 2 The tensile strength is 1000kgf / cm 2 By being equal to or greater than this, breakage during slitting or winding of the electricity storage device tends to be further suppressed, or a short circuit due to a foreign object or the like in the electricity storage device tends to be further suppressed. On the other hand, the tensile strength of the microporous membrane is preferably 5000 kgf / cm 2More preferably, it is 4500 kgf / cm or less. 2 More preferably, it is 4000 kgf / cm or less. 2 The tensile strength of the microporous membrane is 5000 kgf / cm or less. 2 By satisfying this condition, the microporous membrane will relax early during the heat test, weakening the contractile force, and as a result, safety tends to be improved.

[0044] The thickness of the polyolefin microporous membrane is preferably 1.0 μm or more, more preferably 2.0 μm or more, even more preferably 3.0 μm or more, 4.0 μm or more, or 4.5 μm or more, and even more preferably 5.0 μm or more. When the thickness of the microporous membrane is 1.0 μm or more, the membrane strength tends to be further improved. In addition, the thickness of the microporous membrane is preferably 500 μm or less, more preferably 100 μm or less, and even more preferably 80 μm or less, 22 μm or less, or 19 μm or less. When the thickness of the microporous membrane is 500 μm or less, the ion permeability tends to be further improved. The thickness of the microporous membrane can be measured by the method described in the Examples.

[0045] When the polyolefin microporous membrane is used as a separator for a relatively high-capacity lithium-ion secondary battery in recent years, the membrane thickness is preferably 25 μm or less, more preferably 22 μm or less or 20 μm or less, even more preferably 18 μm or less, and particularly preferably 16 μm or less, 14.0 μm or less, or 12.0 μm or less. In this case, the membrane thickness of the microporous membrane is 25 μm or less, and the permeability tends to be further improved. In this case, the lower limit of the membrane thickness may be 1.0 μm or more, 3.0 μm or more, 4.0 μm or more, or 5.0 μm or more.

[0046] The polyolefin microporous membrane may contain, as desired, polyethylene other than UHMWPE, polyolefin other than polyethylene, resins other than polyolefin, various additives, and the like.

[0047] <Ultra-high molecular weight polyethylene (UHMWPE)> Ultra-high molecular weight polyethylene (UHMWPE) refers to polyethylene having a viscosity average molecular weight (Mv) of 300,000 to 9,700,000 and a polydispersity (Mw / Mn), expressed as the ratio of the weight average molecular weight (Mw) to the number average molecular weight (Mn), of 3 to 15.

[0048] The viscosity average molecular weight (Mv) of the UHMWPE is preferably 320,000 to 9,000,000, and more preferably 350,000 to 8,500,000. The dispersity of the UHMWPE is preferably 3-15, 4-14, or 4-13.

[0049] While the viscosity average molecular weight (Mv) can be measured with good accuracy and reproducibility regardless of the molecular weight, the number average molecular weight (Mn), weight average molecular weight (Mw), and the degree of dispersion (Mw / Mn) expressed as a ratio thereof obtained by GPC measurement cannot be measured accurately in the molecular weight range of 1 million or more because of the column exclusion volume limit. On the other hand, in the molecular weight range of 1 million or less, it can be measured with very good accuracy and reproducibility, and the number average molecular weight (Mn), weight average molecular weight (Mw), and the degree of dispersion (Mw / Mn) expressed as a ratio thereof can be calculated. In addition, verification experiments in the molecular weight range of 1 million or less have experimentally clarified that when the same type of polyethylene polymerization catalyst is used, the degree of dispersion (Mw / Mn) does not change even if the number average molecular weight (Mn) and weight average molecular weight (Mw) change. Therefore, in the present invention, while it is impossible to accurately measure the number average molecular weight (Mn) and weight average molecular weight (Mw) of UHMWPE with a molecular weight of 1 million or more, the dispersity expressed as the ratio between them (Mw / Mn) was examined using values ​​calculated in the range of 1 million or less polymerized using the same type of polyethylene polymerization catalyst.

[0050] In the first and second embodiments, single or multiple types of UHMWPE may be used. From the perspective of the high strength of the polyolefin microporous membrane, UHMWPE is preferably poly(ethylene and / or propylene-co-α-olefin), more preferably at least one selected from the group consisting of poly(ethylene-co-propylene), poly(ethylene-co-butene), and poly(ethylene-co-propylene-co-butene). From a similar perspective, UHMWPE preferably contains structural units derived from ethylene in an amount of 98.5 mol% or more and 100 mol% or less, and more preferably contains structural units derived from α-olefins other than ethylene in an amount of more than 0.0 mol% and 1.5 mol% or less.

[0051] From the perspective of high strength, the mass ratio of UHMWPE is preferably 5% by mass to 70% by mass, more preferably 7% by mass to 68% by mass, based on the total mass of all the powder raw materials of the polyolefin microporous membrane.

[0052] <Polyethylene other than UHMWPE> Examples of polyethylene other than UHMWPE include high-density polyethylene (HDPE), linear low-density polyethylene (LLDPE), low-density polyethylene by high-pressure method, or mixtures thereof. Further, polyethylene with a narrow molecular weight distribution obtained using a metallocene catalyst or HDPE obtained by multi-stage polymerization may be used. These polyethylenes can be used singly or in plurality and can constitute the remainder of the polyolefin microporous membrane containing UHMWPE.

[0053] <Polyolefins other than polyethylene> Examples of polyolefins other than polyethylene include polypropylene, polybutene, ethylene-propylene copolymer, polymethylpentene, silane-grafted modified polyolefin, etc. These polyolefins can be used singly or in plurality and can constitute the remainder of the polyolefin microporous membrane containing UHMWPE.

[0054] <Resins other than polyolefins> Examples of resins other than polyolefins include engineering plastic resins such as polyphenylene ether; polyamide resins such as nylon 6, nylon 6-12, and aramid resin; polyimide resins; polyester resins such as polyethylene terephthalate (PET) and polybutene terephthalate (PBT); polycarbonate resins; fluorine resins such as polyvinylidene fluoride (PVDF) and polytetrafluoroethylene; copolymers of ethylene and vinyl alcohol, C 2 ~C 12 Examples of the thermoplastic resin include a copolymer of α-olefin and carbon monoxide and a hydrogenated product thereof; a hydrogenated styrene-based polymer; a copolymer of styrene and α-olefin and a hydrogenated product thereof; a copolymer of styrene and an aliphatic monounsaturated fatty acid; a polymer of (meth)acrylic acid, (meth)acrylate and / or a derivative thereof; a copolymer of styrene and a conjugated diene-based unsaturated monomer and a hydrogenated product thereof; polysulfone, polyethersulfone, polyketone, etc. These resins may be used singly or in combination, and may constitute the remainder of the polyolefin microporous membrane containing UHMWPE.

[0055] <Additives> The polyolefin microporous membrane may contain, in addition to UHMWPE, known additives such as a dehydration condensation catalyst, a metal soap such as calcium stearate or zinc stearate, an ultraviolet absorber, a light stabilizer, an antistatic agent, an antifogging agent, and a coloring pigment, if desired.

[0056] <Production method of polyolefin microporous membrane> As long as the polyolefin microporous membrane has the above-described crystal structure, it may be produced by any method known in the art. For example, the polyolefin membrane may be formed by melt extrusion of a polyolefin resin, followed by stretching, and the like, and the porosity may be made by a wet method. An example of a wet method is a method in which a pore-forming material such as a plasticizer is added to a polyolefin, dispersed, and molded, and then the pore-forming material is extracted with a solvent or the like to form pores, and stretching is performed before or after extraction as necessary.

[0057] One example of a means for controlling the polyethylene crystallinity of a polyolefin microporous membrane measured by XRD to within a range of 80 to 99% and the polyethylene crystallite size to within a range of 14.2 to 40.0 nm is to adjust the resin composition in the raw materials for the polyolefin microporous membrane, to perform extrusion, kneading and molding using a mixed slurry of a liquid plasticizer such as liquid paraffin and UHMWPE to make the molded product porous by a wet method, and the like.

[0058] The method for producing a polyolefin microporous membrane according to the third embodiment includes the following steps: (1) Temperature: 20℃~70℃, 100 seconds -1 ~400,000 seconds -1 a mixed slurry production step of mixing a polyolefin powder containing polyethylene (PE) and a plasticizer using a continuous mixer under conditions of a shear rate of 1.0 to 60 seconds and a residence time of 1.0 to 60 seconds to produce a mixed slurry; (2) an extrusion step of feeding the mixed slurry into a twin-screw extruder and extruding it to produce a resin composition; (3) a step of extruding the resin composition into a sheet, cooling and solidifying it to process it into a sheet-like molded product; (4) biaxially stretching the sheet-like molded body at an areal magnification of 20 times or more and 200 times or less to form a stretched product; (5) extracting the plasticizer from the stretched product to form a porous body; and (6) a step of heat-treating the porous body at a temperature equal to or lower than the melting point of the porous body to stretch the porous body; Includes.

[0059] Without wishing to be bound by theory, by subjecting a mixed slurry of PE and a plasticizer obtained in (1) the mixed slurry production process to (2) the extrusion process, (3) the sheet processing process, (4) the stretching process, (5) the extraction process, and (6) the heat treatment process, a uniform resin composition can be obtained without applying excessive shear force in (2) the extrusion process, so that the generation of unmelted gel or the decrease in molecular weight of a microporous membrane containing PE can be suppressed, and high quality and high strength can be achieved when used as a separator for a lithium ion secondary battery.

[0060] Furthermore, without wishing to be bound by theory, in the third embodiment, by uniformly feeding PE and plasticizer to the extruder in step (2), uniform mixing can be achieved, and it is believed that uniform dispersion of the PE-containing polyolefin powder is ensured in step (1), and the crystallinity of the obtained polyolefin microporous film is increased and stress concentration points are diffused without damaging the higher-order structure of PE by scission of polymer chains with high shear force during melt mixing as in the conventional method.

[0061] Furthermore, in the third embodiment, a uniformly mixed slurry of the PE-containing polyolefin powder and the plasticizer can be subjected to the extrusion process, which may provide better handling properties than supplying the resin powder and liquid separately to an extruder and then dispersing them uniformly.

[0062] Each step of the method for producing a polyolefin microporous membrane according to the third embodiment will be described below. Unless otherwise specified, known conditions or methods can be used for each step.

[0063] [(1) Mixed slurry production process] In step (1), the mixture is mixed in a continuous mixer at a temperature of 20°C to 70°C for 100 seconds. -1 ~400,000 seconds -1 A polyethylene (PE)-containing polyolefin powder and a plasticizer are mixed under the conditions of a shear rate of 1.0 to 60 seconds and a residence time of 1.0 to 60 seconds to obtain a mixed slurry. In step (1), it is preferable to use ultra-high molecular weight polyethylene (UHMWPE) as the PE raw material from the viewpoint of improving the quality and strength of the obtained polyolefin microporous membrane.

[0064] In the raw material UHMWPE powder, when it coexists with a plasticizer, the ratio of crystalline and non-crystalline parts of UHMWPE changes due to heat generation within the system or external heating, and the overall mobility gradually increases, so that the plasticizer can penetrate into the non-crystalline parts of the UHMWPE powder or the intermediate layer between the crystalline and non-crystalline parts. At this stage, the resin powder does not melt or dissolve, and this phenomenon is called swelling of the plasticizer. By swelling the UHMWPE powder to a predetermined level in step (1) before feeding it into the extruder in the extrusion step (2), a uniform dissolved resin composition can be obtained without applying excessive shear to the UHMWPE in the extrusion step (2). In the conventional method that does not include the mixed slurry production step (1), the melting or dissolution of the UHMWPE powder surface progresses when the UHMWPE powder is fed into the extruder, suppressing swelling inside the extruder and significantly inducing the generation of unmelted material or gel.

[0065] In addition, the solid viscoelasticity measurement of the compressed resin of UHMWPE powder showed that the storage modulus (E') showed a broad peak at 0℃ to 120℃. This is called crystalline relaxation, and it is caused by the sliding of crystal grain boundaries (α 1 ) or the crystal itself becomes elastic (α 2 ) [The corresponding temperature T is T α2 >T α1 In addition, UHMWPE powder varies or differs in molecular weight, molecular weight distribution, density, etc., but generally, all of them are T α2 is known to be around 100℃, and the storage modulus (E') shows a large peak near 60℃, 1 is observed. 2 From this, in order to maximize the swelling of UHMWPE powder without melting it, it is possible to selectively create a slip state at the crystal grain boundaries without causing the crystals themselves to change in elasticity at 70°C to 100°C, and to promote the swelling of the plasticizer in the non-crystalline portion or the intermediate layer between the crystalline and non-crystalline portions. Also, at temperatures above 70°C, the crystals gradually melt, inhibiting swelling.

[0066] In view of the above, the lower limit of the set temperature of the continuous mixer is 20°C or more, preferably 25°C or more, and more preferably 30°C or more, from the viewpoint of maximizing swelling of the PE powder, and the upper limit is 70°C or less, preferably 68°C or less, and more preferably 67°C or less, 66°C or less, or 65°C or less, from the viewpoint of suppressing dissolution of UHMWPE during mixing and obtaining a slurry. The shear rate of the continuous mixer was set to 100 s from the viewpoint of uniformly contacting the PE-containing polyolefin powder with the plasticizer and obtaining a dispersion. -1 ~400,000 seconds -1 and preferably 120 seconds -1 ~398,000 seconds -1 , more preferably 1,000 seconds -1 ~100,000 seconds -1 It is. The residence time in the continuous mixer is from 1.0 to 60 seconds, preferably from 2.0 to 58 seconds, and more preferably from 2.0 to 56 seconds, from the viewpoint of ensuring dispersion of PE in the plasticizer.

[0067] The ultra-high molecular weight polyethylene (UHMWPE) used in the third embodiment may be the UHMWPE described above for the first or second embodiments.

[0068] In the third embodiment, a single type or multiple types of UHMWPE may be used. From the viewpoint of high strength of the polyolefin microporous membrane, the UHMWPE is preferably poly(ethylene and / or propylene-co-α-olefin), more preferably at least one selected from the group consisting of poly(ethylene-co-propylene), poly(ethylene-co-butene), and poly(ethylene-co-propylene-co-butene). From the same viewpoint, the UHMWPE preferably contains 98.5 mol% or more and 100 mol% or less of structural units derived from ethylene, and more preferably contains more than 0.0 mol% and 1.5 mol% or less of structural units derived from α-olefins other than ethylene.

[0069] The content of polyolefin powder in the mixed slurry, based on the mass of the mixed slurry, is preferably more than 0 mass%, more preferably 1 mass or more, even more preferably 2 mass or more or 4 mass or more from the viewpoint of the strength of the obtained polyolefin microporous film, and this content is preferably 50 mass or less, more preferably 40 mass or less, even more preferably 30 mass or less or 20 mass or less from the viewpoint of suppressing the generation of unmelted gels in the polyolefin powder.

[0070] The PE or UHMWPE content in the polyolefin powder, based on the mass of the polyolefin powder, is preferably 2 mass% or more, more preferably 4 mass% or more, from the viewpoint of the strength of the obtained polyolefin microporous film, and this content is preferably 90 mass% or less, more preferably 88 mass% or less, from the viewpoint of suppressing the generation of unmelted gels of PE or UHMWPE.

[0071] The plasticizer used in step (1) may be a known material as long as it is liquid at a temperature of 20°C to 70°C and has excellent dispersibility of PE. In consideration of the extraction step (5), the plasticizer used in step (1) is preferably a non-volatile solvent capable of forming a homogeneous solution at or above the melting point of the polyolefin. Specific examples of non-volatile solvents include, for example, liquid paraffin, paraffin wax, decane, decalin, and other hydrocarbons; esters such as dioctyl phthalate and dibutyl phthalate; and higher alcohols such as oleyl alcohol and stearyl alcohol. Among them, liquid paraffin is preferred because it has high compatibility with polyethylene or polypropylene, and even when the molten kneaded product is stretched, the interfacial peeling between the resin and the plasticizer is unlikely to occur, and uniform stretching tends to be easily performed.

[0072] The mixed slurry may contain, as desired, polyethylene other than UHMWPE, polyolefin other than polyethylene, resin other than polyolefin, various additives, etc. Furthermore, the polyolefin powder may contain, as desired, polyethylene other than UHMWPE, and / or polyolefin other than polyethylene.

[0073] Examples of polyethylene other than UHMWPE include high density polyethylene (HDPE), linear low density polyethylene (LLDPE), high pressure low density polyethylene, and mixtures thereof. In addition, polyethylene with a narrow molecular weight distribution obtained by utilizing a metallocene catalyst and HDPE obtained by multi-stage polymerization may be used. These polyethylenes may be used singly or in combination, and may constitute the remainder of the polyolefin microporous membrane containing UHMWPE.

[0074] Examples of polyolefins other than polyethylene include polypropylene, polybutene, ethylene-propylene copolymers, polymethylpentene, silane-grafted polyolefins, etc. These polyolefins may be used singly or in combination, and may constitute the remainder of the polyolefin microporous membrane containing UHMWPE.

[0075] Examples of resins other than polyolefins include engineering plastic resins such as polyphenylene ether; polyamide resins such as nylon 6, nylon 6-12, and aramid resin; polyimide resins; polyester resins such as polyethylene terephthalate (PET) and polybutene terephthalate (PBT); polycarbonate resins; fluorine resins such as polyvinylidene fluoride (PVDF) and polytetrafluoroethylene; copolymers of ethylene and vinyl alcohol, C 2 ~C 12 Examples of the thermoplastic resin include a copolymer of α-olefin and carbon monoxide and a hydrogenated product thereof; a hydrogenated styrene-based polymer; a copolymer of styrene and α-olefin and a hydrogenated product thereof; a copolymer of styrene and an aliphatic monounsaturated fatty acid; a polymer of (meth)acrylic acid, (meth)acrylate and / or a derivative thereof; a copolymer of styrene and a conjugated diene-based unsaturated monomer and a hydrogenated product thereof; polysulfone, polyethersulfone, polyketone, etc. These resins may be used singly or in combination, and may constitute the remainder of the polyolefin microporous membrane containing UHMWPE.

[0076] The mixed slurry may contain known additives such as a dehydration condensation catalyst, metal soaps such as calcium stearate or zinc stearate, an ultraviolet absorber, a light stabilizer, an antistatic agent, an antifogging agent, and a coloring pigment.

[0077] [(2) Extrusion process] In step (2), the mixed slurry is fed into a twin-screw extruder and extruded to obtain a resin composition.

[0078] In step (2), the mixed slurry is preferably fed to a twin-screw extruder at a temperature of 25° C. to 80° C. to produce a resin composition. From the viewpoint of ensuring the appropriate viscosity of the mixed slurry while ensuring entanglement of polymer chains to an extent that does not cause a decrease in the molecular weight of PE contained in the polyolefin powder, the feed temperature is preferably adjusted within the range of 25° C. to 80° C. From the same viewpoint, the feed temperature is more preferably 30° C. to 76° C., and further preferably 30° C. to 70° C.

[0079] In the third embodiment, (1) the mixed slurry production process ensures uniform dispersion of PE, and (2) the extrusion process is not limited by conditions such as the type of twin-screw extruder, supply of the slurry to the twin-screw extruder, extrusion time, extrusion speed, shear rate, shear force, etc., so long as the feed temperature and extrusion temperature are controlled within the ranges described above.

[0080] In order to prevent the generation of unmelted gel or the decrease in molecular weight in the resin composition, it is preferable to swell, melt and / or knead the PE-containing polyolefin powder in the twin-screw extruder. As a melt kneading method, for example, a method in which the mixed slurry is put into the twin-screw extruder to heat and melt the resin components such as the PE-containing polyolefin powder, and then knead them with a plasticizer can be mentioned.

[0081] During extrusion of the mixed slurry, polyethylenes other than UHMWPE, polyolefins other than polyethylene, resins other than polyolefins, various additives, etc. may be fed to the twin-screw extruder as desired. The polyethylenes other than UHMWPE, polyolefins other than polyethylene, resins other than polyolefins, and additives described in (1) the mixed slurry production process can be fed to the twin-screw extruder in (2) the extrusion process.

[0082] [(3) Sheet processing process] In the sheet processing step (3), the resin composition obtained in step (2) is extruded into a sheet and cooled to solidify, thereby forming a sheet-shaped molded product. The resin composition may contain a polyolefin resin including UHMWPE, a plasticizer, etc.

[0083] From the viewpoint of sheet formability, the proportion of the polyolefin resin in the sheet-formed product is preferably 10% by mass to 80% by mass, more preferably 20% by mass to 60% by mass, and most preferably 30% by mass to 50% by mass, based on the mass of the sheet-formed product.

[0084] As a method for producing a sheet-shaped molded product, for example, the resin composition obtained in step (2) is extruded into a sheet through a T-die or the like, and is brought into contact with a heat conductor to cool to a temperature lower than the crystallization temperature of the resin component and solidified. Examples of heat conductors used for cooling and solidifying include metal, water, air, plasticizers, and the like. Among these, it is preferable to use a metal roll because of its high thermal conductivity. In addition, when the extruded resin composition is brought into contact with a metal roll, it is also preferable to sandwich it between the rolls because this further increases the efficiency of thermal conduction, and the sheet is oriented to increase the film strength and tends to improve the surface smoothness of the sheet. When the resin composition is extruded into a sheet from a T-die, the die lip interval is preferably 200 μm or more and 3,000 μm or less, and more preferably 500 μm or more and 2,500 μm or less. When the die lip interval is 200 μm or more, the amount of scum is reduced, and the influence on the film quality such as streaks or defects is small, and the risk of film breakage in the subsequent stretching process can be reduced. On the other hand, if the die lip distance is 3,000 μm or less, the cooling rate is fast, which prevents uneven cooling and maintains the thickness stability of the sheet.

[0085] In addition, during the step (3), the extruded sheet-like molded product may be rolled.

[0086] [(4) Stretching process] In step (4), the sheet-like molded article obtained in step (3) is biaxially stretched at an areal stretching ratio of 20 to 200 times to obtain a stretched product.

[0087] As the stretching process, biaxial stretching is preferred over uniaxial stretching from the viewpoint of reducing the film thickness distribution and air permeability distribution in the width direction. By simultaneously stretching the sheet in two axial directions, the number of times the sheet-like molded body is cooled and heated repeatedly during the film-forming process is reduced, and the distribution in the width direction is improved. Examples of the biaxial stretching method include simultaneous biaxial stretching, sequential biaxial stretching, multi-stage stretching, and multiple stretching. From the viewpoint of improving the puncture strength and uniformity of stretching, simultaneous biaxial stretching is preferred, and from the viewpoint of easy control of the plane orientation, sequential biaxial stretching is preferred.

[0088] In this specification, simultaneous biaxial stretching refers to a stretching method in which stretching in MD (machine direction of continuous microporous membrane molding) and stretching in TD (direction crossing the MD of the microporous membrane at an angle of 90°) are performed simultaneously, and the stretching ratios in each direction may be different. Sequential biaxial stretching refers to a stretching method in which stretching in MD and TD is performed independently, and while stretching is performed in MD or TD, the other direction is in an unconstrained state or fixed at a fixed length.

[0089] The stretching ratio is in the range of 20 to 200 times in area ratio, preferably in the range of 25 to 170 times, and more preferably in the range of 30 to 150 times. The stretching ratio in each axial direction is preferably in the range of 2 to 15 times in MD and 2 to 15 times in TD, more preferably in the range of 3 to 12 times in MD and 3 to 12 times in TD, and even more preferably in the range of 5 to 10 times in MD and 5 to 10 times in TD. When the total area ratio is 20 times or more, the obtained microporous membrane tends to have sufficient strength, while when the total area ratio is 200 times or less, membrane breakage in step (4) is prevented and high productivity tends to be obtained.

[0090] The stretching temperature is preferably 90°C to 150°C, more preferably 100°C to 140°C, and even more preferably 110°C to 130°C, from the viewpoints of the meltability and film-forming properties of the polyolefin resin.

[0091] [(5) Extraction process] In step (5), the plasticizer is extracted and removed from the stretched product obtained in step (4) to obtain a porous body. For example, the method of extracting the plasticizer includes a method of immersing the stretched product in an extraction solvent to extract the plasticizer and drying the product. The extraction method may be either a batch method or a continuous method. In order to suppress the shrinkage of the porous body, it is preferable to restrain the end of the sheet-like molded product during the series of immersion and drying steps. In addition, it is preferable that the amount of plasticizer remaining in the porous body is less than 1 mass% with respect to the mass of the entire porous film. After the extraction step (5), the plasticizer may be recovered by distillation or other procedures and reused.

[0092] As the extraction solvent, it is preferable to use one that is a poor solvent for polyolefin resins, a good solvent for plasticizers, and has a boiling point lower than the melting point of polyolefin resins. Examples of such extraction solvents include hydrocarbons such as n-hexane and cyclohexane; halogenated hydrocarbons such as methylene chloride and 1,1,1-trichloroethane; non-chlorine halogenated solvents such as hydrofluoroethers and hydrofluorocarbons; alcohols such as ethanol and isopropanol; ethers such as diethyl ether and tetrahydrofuran; and ketones such as acetone and methyl ethyl ketone. These extraction solvents may be recovered and reused by operations such as distillation.

[0093] [(6) Heat treatment process] In step (6), the porous body is heat-treated at a temperature equal to or lower than the melting point of the porous body for the purposes of suppressing shrinkage, heat fixing, etc., and stretching the porous body to obtain a microporous membrane.

[0094] The porous body is subjected to a heat treatment for the purpose of heat setting in order to suppress shrinkage. Examples of the heat treatment method include a stretching operation performed in a predetermined atmosphere at a predetermined temperature and at a predetermined stretch ratio for the purpose of adjusting physical properties, and / or a relaxation operation performed in a predetermined atmosphere at a predetermined temperature and at a predetermined relaxation ratio for the purpose of reducing stretching stress. The relaxation operation may be performed after the stretching operation. These heat treatments can be performed using a tenter or roll stretching machine.

[0095] From the viewpoint of increasing the strength and porosity of the microporous membrane, the stretching operation is preferably performed at least 1.1 times, more preferably at least 1.2 times, the MD and / or TD of the membrane. The relaxation operation is a shrinking operation in the MD and / or TD of the membrane. The relaxation rate is a value obtained by dividing the membrane dimension after the relaxation operation by the membrane dimension before the relaxation operation. When both MD and TD are relaxed, the relaxation rate is a value obtained by multiplying the relaxation rate in MD and the relaxation rate in TD. The relaxation rate is preferably 1.0 or less, more preferably 0.97 or less, and even more preferably 0.95 or less. From the viewpoint of membrane quality, the relaxation rate is preferably 0.5 or more. The relaxation operation may be performed in both MD and TD, or in only one of MD and TD.

[0096] The temperature of the heat treatment including the stretching or relaxation operation is preferably within the range of 100°C to 170°C from the viewpoint of the melting point (hereinafter also referred to as "Tm") of the polyolefin resin. The temperature of the stretching and relaxation operation within the above range is preferable from the viewpoint of the balance between the reduction of the thermal shrinkage rate and the porosity. The lower limit of the heat treatment temperature is more preferably 110°C or more, further preferably 120°C or more, and even more preferably 125°C or more, and the upper limit is more preferably 160°C or less, further preferably 150°C or less, and even more preferably 140°C or less.

[0097] During or after step (6), the microporous membrane may be subjected to post-treatment such as hydrophilization treatment with a surfactant, etc., crosslinking treatment with ionizing radiation, etc. The order of steps (4), (5), and (6) described above may be rearranged or these steps may be performed simultaneously, but from the viewpoint of film formability, it is preferable to perform these steps in the order of steps (4), (5), and (6) using a biaxial stretching machine. From the viewpoints of handling and storage stability, the obtained microporous membrane can be wound up by a winder to form a roll, or cut by a slitter.

[0098] Moreover, by carrying out the method according to the third embodiment, the polyolefin microporous membrane according to the second embodiment can also be produced.

[0099] <Method for producing separator for power storage device> The polyolefin microporous membrane according to the second or third embodiment can be used to manufacture the separator for an electricity storage device according to the first embodiment. The polyolefin microporous membrane can be used as a flat membrane to form a monolayer separator. A separator laminate membrane can be formed by stacking a plurality of polyolefin microporous membranes and / or stacking a polyolefin microporous membrane with another membrane / layer. A separator coating membrane can be formed by coating a polyolefin microporous membrane with paint.

[0100] <Electricity storage device> The separator according to the first embodiment, or the separator including the polyolefin microporous membrane according to the second or third embodiment, can be used in an electricity storage device. The electricity storage device includes a positive electrode, a negative electrode, a separator disposed between the positive and negative electrodes, and an electrolyte. Specific examples of the electricity storage device include lithium batteries, lithium secondary batteries, lithium ion secondary batteries, sodium secondary batteries, sodium ion secondary batteries, magnesium secondary batteries, magnesium ion secondary batteries, calcium secondary batteries, calcium ion secondary batteries, aluminum secondary batteries, aluminum ion secondary batteries, nickel hydrogen batteries, nickel cadmium batteries, electric double layer capacitors, lithium ion capacitors, redox flow batteries, lithium sulfur batteries, lithium air batteries, and zinc air batteries. Among these, from the viewpoint of practicality, lithium batteries, lithium secondary batteries, lithium ion secondary batteries, nickel hydrogen batteries, or lithium ion capacitors are preferred, and lithium batteries or lithium ion secondary batteries are more preferred.

[0101] <Lithium-ion secondary battery> Lithium-ion secondary batteries consist of a positive electrode made of lithium transition metal oxides such as lithium cobalt oxide and lithium cobalt composite oxide, a negative electrode made of carbon materials such as graphite, and an electrolyte such as LiPF 6It is a storage battery that uses an organic solvent containing lithium salts such as lithium ion salts. When charging and discharging a lithium-ion secondary battery, ionized lithium travels back and forth between the electrodes. In addition, since it is necessary for the ionized lithium to move relatively quickly between the electrodes while suppressing contact between the electrodes, a separator is placed between the electrodes. EXAMPLES

[0102] The present embodiment will be described in more detail with reference to examples and comparative examples, but the present embodiment is not limited to the following examples as long as it does not depart from the gist of the present embodiment. The physical properties of the examples and comparative examples were measured by the following methods.

[0103] <Weight average molecular weight (Mw), number average molecular weight (Mn)> A calibration curve was created by measuring standard polystyrene under the following conditions using a Waters ALC / GPC 150C (trademark). Chromatograms were also measured under the same conditions for each of the following polymers, and the weight-average molecular weight and number-average molecular weight of each polymer were calculated based on the calibration curve by the following method. Column: Tosoh GMH 6 -HT (trademark) 2 pieces + GMH 6 -2 HTL (trademark) Mobile phase: o-dichlorobenzene Detector: Differential refractometer Flow rate: 1.0ml / min Column temperature: 140℃ Sample concentration: 0.1wt% (Weight average molecular weight and number average molecular weight of polyethylene) Each molecular weight component in the obtained calibration curve was multiplied by 0.43 (Q factor of polyethylene / Q factor of polystyrene=17.7 / 41.3) to obtain a molecular weight distribution curve converted into polyethylene, and the weight average molecular weight and number average molecular weight were calculated.

[0104] <Viscosity average molecular weight (Mv)> Based on ASTM-D4020, the intrinsic viscosity [η] in decalin solvent at 135°C was determined. The Mv of polyethylene was calculated using the following formula. [η]=6.77×10 -4 Mv 0.67 The Mv of polypropylene was calculated using the following formula. [η]=1.10×10 -4 Mv 0.80

[0105] <Melting point (℃)> The melting points of the polyolefin resins were measured using a differential scanning calorimeter (DSC) measuring device "DSC-60" (manufactured by Shimadzu Corporation).

[0106] <Thickness of each layer (μm)> The film thickness was measured using a Toyo Seiki Micro Thickness Meter (Type KBN, terminal diameter Φ5 mm) at an ambient temperature of 23 ± 2° C. When measuring the thickness, 10 microporous membranes were stacked and measured, and the total thickness was divided by 10 to determine the thickness of one membrane.

[0107] <Porosity (%)> A 10 cm x 10 cm square sample was cut from the microporous membrane and its volume (cm 3 ) and mass (g), and then calculate the density (g / cm 3 ) and the porosity was calculated using the following formula: The density of the mixed composition was determined by calculating the density of each of the raw materials used and the mixing ratio. Porosity (%) = (volume-mass / density of mixed composition) / volume x 100

[0108] <Air permeability (sec / 100cm 3 )> In accordance with JIS P-8117 (2009), Gurley air permeability tester manufactured by Toyo Seiki Co., Ltd. The air permeability of the samples was measured using a meter, G-B2 (trademark).

[0109] <(110) crystallite size, crystallinity> (measurement) XRD measurements were performed using a Rigaku X-ray diffractometer Ultima-IV. Cu-Kα radiation was incident on the sample, and diffracted light was detected by a Rigaku detector D / tex Ultra. KRD measurements were performed under conditions of a sample-detector distance of 285 mm, an excitation voltage of 40 kV, and a current of 40 mA. A focusing optical system was used, and measurements were performed under slit conditions of DS=1 / 2°, SS=open, and vertical slit=10 mm.

[0110] (analysis) The range of the obtained XRD profile from 2θ=9.7° to 2θ=29.0° was separated into three peaks, the orthorhombic (110) diffraction peak, the orthorhombic (200) diffraction peak, and the amorphous peak. The crystallite size was calculated from the full width at half maximum of the (110) diffraction peak according to Scherrer's formula (Formula 1). The (110) diffraction peak and the (200) diffraction peak were approximated by a Voigt function, and the amorphous peak was approximated by a Gaussian function. The peak position of the amorphous peak was fixed at 2θ=19.6°, and the full width at half maximum was fixed at 6.3°, while the peak position and full width at half maximum of the crystalline peak were not fixed. The crystallite size was calculated from the full width at half maximum of the (110) diffraction peak calculated by peak separation according to Scherrer's formula (Formula 1). D(110)=Kλ / (βcosθ) Equation 1 Explanation of symbols in formula 1 D(110): Crystallite size (nm) K: 0.9 (constant) λ: wavelength of X-rays (nm) β:(β 1 2 -β 2 2 ) 0.5 β 1 : Full width at half maximum (rad) of the (hkl) peak calculated as a result of peak separation β 2 : Full width at half maximum of incident beam divergence (rad) θ: Bragg angle In addition, as necessary, the area ratio R was calculated according to the following formula using the area I(110) of the (110) plane diffraction peak and the area I(200) of the (200) plane diffraction peak obtained by this analysis. Area ratio R = I(110) / {I(110)+I(200)} The crystallinity (X) was calculated according to the following formula. Crystallinity X={I(110)+I(200)} / {I(110)+I(200)+Iamr} Iamr: Area of ​​amorphous peak

[0111] <Cross-sectional orientation> (measurement) Wide-angle X-ray scattering measurements were performed using the transmission method with a Rigaku NANO-Viewer X-ray structure evaluation system. The sample was irradiated with CuKα radiation, and scattering was detected using an imaging plate. Wide-angle X-ray scattering measurements were performed under conditions of a sample-detector distance of 95.2 mm, output of 60 kV, and 45 mA. A point focus was used for the optical system, and measurements were performed under the following slit diameters: 1st slit: φ=0.4 mm, and 2nd slit: φ=0.2 mm. The sample was set so that the sample surface formed an angle of 10.5° with the X-ray incidence direction.

[0112] (analysis) The direction normal to the sample surface facing the upstream side projected onto the detector surface is defined as the azimuth angle φ = 0°, and the azimuth angles φ = -180° to φ = 180° are defined clockwise on the detector surface. Next, detector background correction and empty cell scattering correction were performed on the X-ray scattering pattern obtained from the imaging plate. Then, the integrated intensity I(φ) in the range of 19.5° < 2θ < 21.3° where the polyethylene (110) plane diffraction peak exists at each azimuth angle φ is plotted against the azimuth angle φ in the range of azimuth angles -45° < φ < 45°. I(φ) will be a single peak centered at φ = 0° if the molecular chains are oriented parallel to the film surface in the cross section. This curve was fitted by adding a constant and a Gaussian function as shown in Equation 2, and the cross-sectional orientation degree f was calculated according to Equation 3 from the full width at half maximum of the Gaussian function of the fitting result. I(φ)=A+B*exp(-((φ-φ 0 ) / w) 2 ) Equation 2 Explanation of symbols in formula 2 I(φ): Integrated intensity in the range of 19.5°<2θ<21.3° at a certain azimuth angle φ after background correction and empty cell scattering correction φ: Azimuth (rad) f=1-FWHM / 180 Equation 3 Explanation of symbols in formula 3 f: Degree of cross-sectional orientation FWHM: Full width at half maximum of the Gaussian function obtained from the fitting result (°)

[0113] <pore diameter> (measurement) Small angle X-ray scattering measurements were performed using the transmission method with a Rigaku X-ray structure evaluation system NANO-Viwer. The sample was irradiated with CuKα radiation, and scattering was detected with a Dectris semiconductor detector PILATUS. Measurements were performed under conditions of a sample-detector distance of 841.5 mm, output of 60 kV, and 45 mA. A point focus was used for the optical system, and measurements were performed under the following slit diameters: 1st slit: φ=0.4 mm, 2nd slit: φ=0.2 mm, and guard slit: φ=0.8 mm. The sample was set so that the sample surface was perpendicular to the X-ray incidence direction.

[0114] (analysis) The X-ray scattering pattern obtained from PILATUS was subjected to absolute intensity correction of the detector, and the SAXS profile I(q) was obtained by circular averaging. -1 <q<1.04nm -1 The range is fitted by the Porod law shown in Equation 4, and the 3 The specific surface area S per unit area was obtained. Then, assuming that the pores in the membrane are all spherical, the pore diameter d was obtained from the specific surface area S and porosity P using Equation 5. I(q)=2πΔρ e 2 Sq -4 formula 4 Explanation of symbols in formula 4 I(q): Absolute intensity corrected SAXS profile (e 2 / nm 3 ) q: Absolute value of the scattering vector (nm-1 ) Δρ e : electron density difference between air and membrane (e / nm 3 ) S: 1 nm 3 Specific surface area per nm 2 ) d=3P / 50S Equation 5 Explanation of symbols in formula 5 d: Pore diameter (nm) P: Porosity (%) S: 1 nm 3 Specific surface area per nm 2 )

[0115] <Piercing strength (GF)> The puncture strength was determined by carrying out a puncture test on the sample film using a handy compression tester "KES-G5" (manufactured by Kato Tech, trademark) under conditions of a needle tip curvature radius of 0.5 mm and a puncture speed of 2 mm / sec.

[0116] <Tensile breaking strength (kgf / cm 2 )> Using a tensile tester and a sample film cut to a size of 10 mm x 100 mm, the tensile strength of the sample film was measured under the conditions of a load cell load of 5 kgf and a chuck distance of 50 mm.

[0117] <Quantification of resin aggregates in separators> The resin aggregates (gel-containing substances) in the separator are defined as regions having an area of ​​100 μm length×100 μm width or more and through which light does not pass, when the separator obtained through the film-forming process of the examples and comparative examples described below is observed with a transmission optical microscope. 2 The number of resin aggregates per unit area was measured.

[0118] <Quantification of molecular weight degradation> A certain amount of the mixed raw material before being fed into the extruder is measured, and the viscosity [η] is measured using the viscosity average molecular weight measurement method described in the above item <Viscosity average molecular weight (Mv)>. This is called [η 0In addition, the final film obtained in the film-forming process was weighed in the same amount, and the viscosity was measured to obtain [η a Calculate the molecular weight deterioration rate (%) according to the following formula. Molecular weight deterioration rate (%)=100×[η a ] / [η 0 ]

[0119] <Compression resistance test> Two separators were cut to 10cm x 10cm, stacked, and the thickness was measured at 9 arbitrary points within an area of ​​8cm x 8cm based on the intersection of the diagonal lines when viewed from above, and the average value was calculated. Then, the laminate was covered with two PET films (10cm x 10cm) from above and below to form a laminate. Furthermore, the laminate was sandwiched between two rubber sheets (10cm x 10cm) with a thickness of 5mm from above and below, and pressure was applied while heating using a mini test press (product number: MP-WCH) manufactured by TOYOSEIKI. The PET film and rubber sheet were used so that pressure was applied uniformly over the entire surface, and the uniformity was confirmed with a pressure sensor. The temperature of the upper and lower heaters of the press was 70°C, and the sample of 10cm x 10cm was held for 3 minutes so that 8Mpa was applied uniformly to the sample. After the heat compression operation, the thickness of the two stacked separators was measured at any 9 points within an area of ​​8 cm × 8 cm, based on the intersection of the diagonals when viewed from above, and the average value was calculated. The difference from the thickness before the compression operation was quantified as the thickness reduction rate (%) according to the following formula. Thickness reduction rate (%) = ((thickness after compression (μm) - thickness before compression (μm)) / thickness before compression (μm)) * 100

[0120] <Battery Destruction Safety Test> In the battery destruction safety test, an iron nail is driven into a battery charged to 4.5V at a speed of 20mm / sec, penetrating it and causing an internal short circuit. This test can clarify the phenomenon that occurs during an internal short circuit by measuring the time change behavior of the voltage drop of the battery due to an internal short circuit and the behavior of the rise in the battery surface temperature due to an internal short circuit. In addition, insufficient shutdown function of the separator or rupture at low temperatures during an internal short circuit may cause the battery to suddenly heat up, which may cause the electrolyte to ignite and the battery to smoke and / or explode.

[0121] (Preparation of batteries for use in battery destruction safety tests) a. Preparation of the positive electrode Lithium cobalt composite oxide (LiCoO) as a positive electrode active material 2 A slurry was prepared by dispersing 92.2 mass% of the active material, 2.3 mass% each of flake graphite and acetylene black as conductive materials, and 3.2 mass% of polyvinylidene fluoride (PVDF) as a binder in N-methylpyrrolidone (NMP). This slurry was applied to one side of an aluminum foil with a thickness of 20 μm, which serves as a positive electrode current collector, using a die coater, dried at 130° C. for 3 minutes, and then compression molded using a roll press. At this time, the amount of active material applied to the positive electrode was 250 g / m 2 , the bulk density of the active material is 3.00 g / cm 3 It was adjusted to be.

[0122] b. Preparation of the negative electrode A slurry was prepared by dispersing 96.9% by mass of artificial graphite as the negative electrode active material, and 1.4% by mass of ammonium salt of carboxymethylcellulose and 1.7% by mass of styrene-butadiene copolymer latex as the binder in purified water. This slurry was applied to one side of a 12 μm-thick copper foil as the negative electrode current collector using a die coater, dried at 120° C. for 3 minutes, and then compression molded using a roll press. At this time, the amount of the active material applied to the negative electrode was 106 g / m 2 , the bulk density of the active material is 1.35 g / cm 3 It was adjusted to be.

[0123] c. Preparation of non-aqueous electrolyte In a mixed solvent of ethylene carbonate:ethyl methyl carbonate = 1:2 (volume ratio), LiPF 6 was dissolved to a concentration of 1.0 mol / L.

[0124] d. Battery assembly The separator was cut to 60 mm in the transverse (TD) direction and 1000 mm in the longitudinal (MD) direction, folded zigzag around the separator, and the positive and negative electrodes were alternately stacked between the separators (12 positive electrodes, 13 negative electrodes). The positive electrodes had an area of ​​30 mm x 50 mm, and the negative electrodes had an area of ​​32 mm x 52 mm. The zigzag laminate was placed in a laminated bag, and the nonaqueous electrolyte obtained in c. above was poured in and sealed. After leaving it at room temperature for one day, the battery was charged at a current value of 3 mA (0.5 C) in an atmosphere of 25°C up to a battery voltage of 4.2 V, and the current value was started to be reduced from 3 mA so as to maintain 4.2 V after reaching that voltage, for a total of 6 hours, in the first charge after the battery was made. Then, the battery was discharged at a current value of 3 mA (0.5 C) down to a battery voltage of 3.0 V.

[0125] (Maximum heat release rate) After an iron nail was inserted into the resulting battery, the battery surface temperature was measured over a period of 300 seconds using a thermocouple. From the temperature change graph, the rate at which the temperature rise per second was the greatest was determined to be the maximum heat generation rate.

[0126] (Voltage drop time) An iron nail was inserted into the resulting battery, and the time required for the voltage to drop from 4.5 V to 3 V was determined as the voltage drop time (3 V drop time).

[0127] <Evaluation of cycle characteristics and method of fabricating the battery> A battery for evaluating cycle characteristics was prepared according to the same methods as a. to c. in the battery preparation method used in the above item <Battery Destruction Safety Test>, except that the assembly was performed according to d. below. The obtained battery was charged and discharged for 100 cycles in an atmosphere of 60°C. The battery was charged at a current value of 6.0mA (1.0C) up to a battery voltage of 4.2V, and then the current value was reduced from 6.0mA to maintain the battery voltage at 4.2V, for a total of 3 hours. The battery was discharged at a current value of 6.0mA (1.0C) down to a battery voltage of 3.0V. The capacity retention rate was calculated from the discharge capacity at the 100th cycle and the discharge capacity at the 1st cycle. A battery with a high capacity retention rate was evaluated as having good cycle characteristics. d. Battery assembly The separator was cut into a circle with a diameter of 18 mm, and the positive and negative electrodes were cut into a circle with a diameter of 16 mm. The positive electrode, separator, and negative electrode were stacked in this order so that the active material surfaces of the positive and negative electrodes faced each other, and then stored in a stainless steel metal container with a lid. The container and the lid were insulated, and the container was in contact with the copper foil of the negative electrode, and the lid was in contact with the aluminum foil of the positive electrode. The nonaqueous electrolyte obtained in c. of the above item "(7) Battery Destruction Safety Test" was poured into this container and sealed. After leaving it at room temperature for one day, the battery was charged at a current value of 3 mA (0.5 C) in an atmosphere of 25°C up to a battery voltage of 4.2 V, and after reaching the voltage, the current value was started to be reduced from 3 mA so as to maintain 4.2 V, for a total of 6 hours, in the first charging after the battery was made. Then, the battery was discharged at a current value of 3 mA (0.5 C) down to a battery voltage of 3.0 V.

[0128] <Experimental Group I>

[0129] <Film production example> A mixture of 35% by mass of homopolymer ultra-high molecular weight polyethylene (UHMWPE, weight average molecular weight and number average molecular weight cannot be measured, viscosity average molecular weight: 2.5 million), 60% by mass of homopolymer high density polyethylene (HDPE, weight average molecular weight: 130,000, number average molecular weight: 20,000, viscosity average molecular weight: 350,000), 5% by mass of homopolymer polypropylene (PP, weight average molecular weight: 400,000, number average molecular weight: 30,000, viscosity average molecular weight: 350,000), and 1% by mass of pentaerythrityl-tetrakis-[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate] as an antioxidant, based on the total amount of the polyolefin mixture, was added, and liquid paraffin (kinetic viscosity at 37.78°C: 7.59 × 10 -5 m2 The mixture was mixed or dispersed with polyethylene (polyethylene) in a continuous mixer (100 / s) to obtain a mixed slurry (provided that the mixed slurry contained 35% by mass of polyethylene). The obtained mixed slurry was fed to a twin-screw extruder by a feeder. The mixed slurry was melt-kneaded in the extruder, and the feeder and pump were adjusted so that the liquid paraffin ratio in the extruded polyolefin composition was 70% by mass (i.e., the polymer concentration was 30% by mass). The melt-kneading conditions were a set temperature of 230°C, a screw rotation speed of 240 rpm, and a discharge rate of 18 kg / hr. Next, the molten mixture was extruded through a T-die onto a cooling roll whose surface temperature was controlled to 25° C., to obtain a gel sheet having a thickness of 1,400 μm. Next, the gel sheet was introduced into a simultaneous biaxial tenter stretching machine and biaxially stretched under the set stretching conditions of MD magnification of 7.0 times, TD magnification of 6.0 times (i.e., 7×6 times), and biaxial stretching temperature of 125° C. Next, the stretched gel sheet was introduced into a methyl ethyl ketone bath and thoroughly immersed in methyl ethyl ketone to extract and remove the liquid paraffin, and then the methyl ethyl ketone was dried and removed. Next, the microporous membrane was introduced into a TD tenter for heat setting, and HS was performed at a heat setting temperature of 125°C and a stretch ratio of 1.8 times, followed by a relaxation operation of 0.5 times in the TD direction (i.e., the HS relaxation ratio was 0.5 times).Then, the end of the obtained microporous membrane was cut and wound up into a mother roll with a width of 1,100 mm and a length of 5,000 m.

[0130] <Examples I-1 to I-23 and Comparative Examples I-1 to I-12> Microporous membranes were obtained by changing the resin composition in the raw materials, the mode of raw material feed, XRD, WAXD and SAXS profiles, etc., of the above-mentioned membrane production examples, as shown in Tables 1 to 3. The obtained microporous membranes were subjected to various evaluations according to the above-mentioned evaluation methods, and the evaluation results are also shown in Tables 1 to 3. For the (110) plane of the polyolefin microporous membrane obtained in Example I-1, the relationship between the diffraction angle and the diffraction intensity in X-ray diffraction (XRD) is shown in FIG.

[0131] [Table 1]

[0132] [Table 2]

[0133] [Table 3]

[0134] <Experimental Group II>

[0135] [Example II-1] Using a continuous mixer, the powder shown in Table 4 (weight average molecular weight and number average molecular weight cannot be measured, viscosity average molecular weight 450 Ten thousand Ultra-high molecular weight polyethylene (UHMWPE), high-density polyethylene with a weight-average molecular weight of 126,000, a number-average molecular weight of 20,000, and a viscosity-average molecular weight of 150,000; other PE, homopolypropylene with a weight-average molecular weight of 400,000, a number-average molecular weight of 30,000, and a viscosity-average molecular weight of 350,000 (PP), and liquid paraffin (dynamic viscosity at 37.78°C of 7.59 x 10 -5 m 2 / s) at a shear rate of 40,000 s -1 and a residence time of 20 seconds to obtain a mixed slurry adjusted to a temperature of 65°C. The mixed slurry was prepared so that the mass ratio of the polyolefin powder in the mixed slurry was 35%. The abbreviation "StCa" in the table means calcium stearate. The obtained mixed slurry was fed by a feeder to a twin-screw extruder equipped with a manifold (T-die) with a die lip distance of 1500 μm at 60° C. under a nitrogen atmosphere to extrude the resin composition. At this time, liquid paraffin was injected from the middle stage of the extrusion so that the ratio of liquid paraffin in the resin composition extruded from the extruder was 70% by mass and the temperature of the resin composition was 220° C. Then, the extruded resin composition was extruded through the T-die and cast onto a cooling roll whose surface temperature was controlled at 25° C. to obtain a sheet-like molded product. Next, the film was introduced into a simultaneous biaxial tenter stretching machine, and biaxial stretching was performed to obtain a stretched product. The stretching conditions were set to a stretching areal ratio of 50 to 180 times, and the porosity, air permeability, thickness, or puncture strength were adjusted by adjusting the stretching temperature, heating air volume, or ratio. In Example 1, the biaxial stretching temperature was 125°C. Next, the stretched sheet (stretched product) was thoroughly immersed in dichloromethane to extract and remove the liquid paraffin, and then the dichloromethane was dried and removed to obtain a porous body. Next, the porous body was introduced into a TD tenter to perform heat setting, and heat setting (HS) was performed at 128°C, and then a relaxation operation of 0.5 times in the TD direction (i.e., the HS relaxation rate was 0.5 times).Then, the obtained microporous membrane was evaluated as described above.The evaluation results are shown in Table 4.

[0136] [Examples II-2 to II-19, Comparative Examples II-1 to II-8] In comparison with the above Example II-1, the raw material composition, process conditions, etc. were changed as shown in Tables 4 to 6 to attempt the preparation of a polyolefin microporous membrane, and the physical properties of the obtained membrane were evaluated. The evaluation results are also shown in Tables 4 to 6.

[0137] [Table 4]

[0138] [Table 5]

[0139] [Table 6]

Claims

1. A polyolefin microporous membrane for use in a separator for an electricity storage device, comprising: the polyolefin microporous membrane has a polyethylene crystallinity of 80 to 99% as measured by X-ray diffraction (XRD), a polyethylene crystallite size of 14.2 to 40.0 nm as measured by XRD, and a cross-sectional crystal orientation of 0.80 to 0.99; The porosity of the polyolefin microporous film is 30% or more and 90% or less, and The polyolefin microporous membrane contains ultra-high molecular weight polyethylene (UHMWPE) having a viscosity average molecular weight of 2,500,000 to 4,500,000. Polyolefin microporous membrane.

2. The polyolefin microporous membrane according to claim 1, wherein the polyolefin microporous membrane has a converted average pore diameter calculated according to Porod's law in a small angle X-ray scattering (SAXS) measurement of the polyolefin microporous membrane is 50 to 150 nm.

3. Formula 6 below: 10 μm converted permeability coefficient (J)=air permeability (Pe)÷porosity (Po) (Equation 6) The polyolefin microporous membrane according to claim 1 or 2, having a converted permeability coefficient per 10 μm of membrane thickness, expressed as:

4. The polyolefin microporous membrane according to any one of claims 1 to 3, wherein the UHMWPE is poly(ethylene and / or propylene-co-α-olefin).

5. The polyolefin microporous membrane according to any one of claims 1 to 4, wherein the UHMWPE is at least one selected from the group consisting of poly(ethylene-co-propylene), poly(ethylene-co-butene), and poly(ethylene-co-propylene-co-butene).

6. The polyolefin microporous membrane according to any one of claims 1 to 5, wherein the UHMWPE contains 98.5 mol% or more and 100 mol% or less of structural units derived from ethylene.

7. The polyolefin microporous membrane according to any one of claims 1 to 6, wherein the UHMWPE contains more than 0.0 mol% and not more than 1.5 mol% of structural units derived from an α-olefin other than ethylene.

8. The polyolefin microporous membrane according to any one of claims 1 to 7, wherein the mass ratio of the UHMWPE is 2 mass% to 90 mass% based on the total mass of all powder raw materials of the polyolefin microporous membrane.

9. The polyolefin microporous membrane according to any one of claims 1 to 8, wherein the mass ratio of the UHMWPE is 5 mass% to 70 mass% based on the total mass of all powder raw materials of the polyolefin microporous membrane.

Citation Information

Patent Citations

  • Method for producing porous film

    JP2002088189A

  • Separator for non-aqueous electrolyte secondary battery, laminated separator for non-aqueous electrolyte secondary battery, member for non-aqueous electrolyte secondary batter, non-aqueous electrolyte secondary battery and porous film manufacturing method

    JP2017103044A

  • JPP7351943B

  • Microporous polyolefin film and process for producing the same

    WO2000020492A1

  • Microporous polyolefin film, separator for non-aqueous secondary battery, non-aqueous secondary battery, and process for production of microporous polyolefin film

    WO2011118660A1